ANALISIS KADAR KLOROFIL DAUN CANTIGI (Vaccinium varingiaefolium) BERDASARKAN JARAK DARI KAWAH PAPANDAYAN DI TAMAN WISATA ALAM PAPANDAYAN - Lida Amalia (Jurnal Life Science : Jurnal Pendidikan dan Ilmu Pengetahuan Alam, 2019)
Abstract:"ANALYSIS OF CHLOROPHYLL CONTENT IN CANTIGI LEAF (Vaccinium varingiaefolium) BASED ON DISTANCE FROM PAPANDAYAN CRATER IN NATURE PARK PAPANDAYAN". Plants that are found around the Papandayan Crater are cantigi (Vaccinium varingiaefolium). It is known that the height of the cantigi plant is increasing with increasing distance from the crater. This is due to the conditions around the crater with the amount of sulfur gas released from the crater. Thus, a study was conducted to determine the chlorophyll content of cantigi leaves (Vaccinium varingiaefolium) at different distances from the Papandayan Crater. The method used in this study is descriptive method, with leaf population of cantigi plants (Vaccinium varingiaefolium) in the Papandayan Nature Park. The sample in this study is leaves cantigi plant (Vaccinium varingiaefolium) which are in a radius or distance of 0-25 m (R1), 25-50 m (R2), and 50-75 m (R3) from the Papandayan Crater. Samples were taken randomly as many as 10 leaves from 10 trees in each distance category. Based on the results of the study it can be seen that the average levels of chlorophyll a, chlorophyll b and total chlorophyll at a distance of 0-25 m are 3.60 mg / L, 2.80 mg / L and 6.50 mg / L respectively. At a distance of 25-50 m is 3.79 mg / L, 3.10 mg / L and 6.89 mg / L, while at a distance of 50-75 m is 4.00 mg / L, 3.90 mg / L and 7.90 mg / L. Based on the results of statistical tests it can be seen that there are significant differences. Thus it can be concluded that the distance from the Papadayan crater affects the chlorophyll content of the cantigi leaves, the farther of distance from the crater, the more chlorophyll content.. Keywords: Cantigi Leaf Chlorophyll Content, Distance from Papandayan Crater.